Virtual Gaming as A Contemporary Research Trend for Mental Health Professionals - Baruah, Anganabha (National Journal of Community Medicine, 2023)
As technology continues to be a part of our life, online gaming has claimed the hearts of millions of people as a favourite leisure activity. Among them online role-playing game provides people the opportunity to play a desired role, be it a king, princess or warrior. This article aimed to provide an insight into what role-playing game is, and why it has become so popular in recent years, with the help of existing literature. This article also attempted to point out the need to research more in the field of gaming as the existing literature is not sufficient to cover the vastness of the topic. The digitalization of games from physical form to online form has changed the way games has been viewed, played, and understood. Due to the popularity of online games, there is a significant change in the research around online games, especially role-playing games. There is still more research needed in Indian context about online games as it has become a popular source of entertainment throughout all the ages and also become a huge source of economy.